The Civilizational Approach to the Study of Islam - Noor Ali, Auranzaib (South Asian Journal of Religion and Philosophy (SAJRP), 2023)
The paper explores the study of Islam as a civilization and considers the lived experiences of Muslims from a sociological perspective. The history of Islam is intertwined with world history and consists of many genuine encounters and exchanges between Muslims and non-Muslims. The civilizational approach to the study of Islam indicates that Muslims and Muslim societies were ready to learn from other religious groups. This article will examine the situation in Baghdad and Cordoba during the 10th-century and show how different socio-economic, political, and religious systems were enriched by means of exchanges between diverse religious groups. Instead of becoming involved in debates about doctrine, which can be divisive, the study of Islam from a civilizational perspective can promote understanding and encourage cooperation among different religions.